2023
DOI: 10.1021/acssuschemeng.2c05547
|View full text |Cite
|
Sign up to set email alerts
|

All-pH Hydrogen Evolution by Heterophase Molybdenum Carbides Prepared via Mechanochemical Synthesis

Abstract: As non-precious-metal catalysts for the hydrogen evolution reaction (HER), molybdenum carbides have attracted extensive attention in recent years. Molybdenum carbides usually require high synthesis temperatures (>700 °C), which leads to a high cost. In this study, we report a controllable synthesis of heterophase molybdenum carbides (MoC/Mo2C) using a simple ball milling method without external thermal input. The as-obtained MoC/Mo2C catalysts exhibit excellent HER electrocatalytic activity and durability at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…As revealed in Figure a, the full XPS spectrum confirmed that the sample consisted of Mo, C, and O . As depicted in Figure b, the Mo 3d XPS spectrum can be segmented into four states, namely, Mo 2+ (228.28, 231.60 eV), Mo 3+ (228.89, 232.63 eV), Mo 4+ (230.06, 234.69 eV), and Mo 6+ (233.06, 235.82 eV). There is still controversy with the exact valence states of Mo in MoC and Mo 2 C. Typically, most scholars believe that Mo 2+ is dominant in Mo 2 C and the Mo 3+ is dominant in MoC. In addition, the higher valence states of Mo 4+ and Mo 6+ originate from MoO 2 and MoO 3 , which are caused by partial oxidation at the surface of MoC/Mo 2 C. ,, Figure c displays the C 1s XPS spectrum that can be fitted using four peaks, which are attributed to Mo–C (283.05 eV), C–C (284.80 eV), C–O (286.25 eV), and OC–O (288.48 eV) species. , In addition, evident peaks in the O 1s spectrum of O–H (530.53 eV), CO (531.84 eV), and Mo–O (533.01 eV) were derived from MoO 2 and MoO 3 due to the slight oxidation of the MoC–Mo 2 C surface (Figure d) .…”
Section: Resultsmentioning
confidence: 83%
“…As revealed in Figure a, the full XPS spectrum confirmed that the sample consisted of Mo, C, and O . As depicted in Figure b, the Mo 3d XPS spectrum can be segmented into four states, namely, Mo 2+ (228.28, 231.60 eV), Mo 3+ (228.89, 232.63 eV), Mo 4+ (230.06, 234.69 eV), and Mo 6+ (233.06, 235.82 eV). There is still controversy with the exact valence states of Mo in MoC and Mo 2 C. Typically, most scholars believe that Mo 2+ is dominant in Mo 2 C and the Mo 3+ is dominant in MoC. In addition, the higher valence states of Mo 4+ and Mo 6+ originate from MoO 2 and MoO 3 , which are caused by partial oxidation at the surface of MoC/Mo 2 C. ,, Figure c displays the C 1s XPS spectrum that can be fitted using four peaks, which are attributed to Mo–C (283.05 eV), C–C (284.80 eV), C–O (286.25 eV), and OC–O (288.48 eV) species. , In addition, evident peaks in the O 1s spectrum of O–H (530.53 eV), CO (531.84 eV), and Mo–O (533.01 eV) were derived from MoO 2 and MoO 3 due to the slight oxidation of the MoC–Mo 2 C surface (Figure d) .…”
Section: Resultsmentioning
confidence: 83%
“…In addition, there is a high specific surface area and hierarchical pore structure for Ni-Co/Mo 2 C/Co 6 Mo 6 C 2 @C, which can accelerate material transfer in the process of HER. Therefore, Ni-Co/Mo 2 C/Co 6 Mo 6 C 2 @C demonstrates great superiority for HER in acidic and alkaline conditions, which also excels that of some reported transition-based catalysts for HER (Table S1) [32][33][34][35][36][37][38][39][40][41][42] .…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…As a half-reaction of water splitting, the hydrogen evolution reaction (HER) is a two-electron-proton coupling reaction that takes place on the surface of the cathode catalyst [27,28]. In acidic media, the hydrogen evolution reaction is generally considered to consist Nowadays, many methods have been proposed, such as optimization of synthesis methods [20], composites with carbon material [21], non-precious metal doping [22], transition metal doping [23], construction of heterogeneous structures [24], etc. Among them, the importance of sulphur-doping, Ni-doping, and heterophase structure on molybdenum carbide-based catalysts for enhancement of activity in acidic and basic media has been highlighted in this review.…”
Section: Mechanism Of Hydrogen Evolution Reactionmentioning
confidence: 99%